BACTERIOLOGY OF DIABETIC FOOT IN TERTIARY CARE HOSPITAL; FREQUENCY, ANTIBIOTIC SUSCEPTIBILITY AND RISK FACTORS - Amjad, Syeda Sadia; Zafar, Jamal; Shams, Nadia (Journal of Ayub Medical College Abbottabad, 2017)
Background: Diabetic foot being one of the frequent and disabling complications of diabetes. In view of widespread regional variation in causative organisms and antimicrobial susceptibility, the current study aimed to determine frequency of causative organisms, their antimicrobial susceptibility and associated risk factors. Methods: This descriptive cross-sectional study was conducted in 6 months' duration at dept. of Medicine; PIMS Hospital Islamabad. Type 2 Diabetes mellitus patients with diabetic foot ulcer were enrolled after informed consent. Patients already receiving antibiotics, having no growth on culture and >3 weeks' duration of ulcer were excluded. Sample from wound was sent for culture and sensitivity. Antibiotic susceptibility testing identified the susceptible and resistant strains of organisms. Results: Among 114 patients (66.67% males and 33.33% females); mean age was 55.11±11.96 years. Staphylococcus aureus was identified in 46%, E. coli in 28%, Pseudomonas in 6%, Klebsiella in 3.5% and other organisms in 17%. 92% of S. aureus was sensitive to Vancomycin and 67% to Clindamycin. Amongst E. coli, 81% showed sensitivity to Imipenem, 69% to Aminoglycosides and 31% to Quinolones. Glycaemic control was unsatisfactory in 65.8%. Peripheral vascular disease was found in 46% patients and sensory neuropathy in 94%. Conclusion: Staphylococcus aureus was the most frequent isolate amongst gram positive organisms while E. coli amongst gram-negatives. Vancomycin is suggested to be the drug of choice for gram positive and Imipenem for gram negative organisms. Appropriate antimicrobial therapy according to susceptibility patterns would reduce the morbidity and emergence of multidrug resistant organisms in diabetic foot infections. Keywords: Antibiotic susceptibility; Bacteriology; Diabetic foot; Glycaemic control